Application of PSAK 109 in the Preparation of the Financial Statements of Baznas Pematang Siantar - Intan Fitri Panisa Harahap; Arnida Wahyuni Lubis (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
The Sharia Financial Accounting Standards Board of the Indonesian Accounting Association stipulates Statement of Financial Accounting Standards No. 109 concerning Accounting for Zakat and Infaq/Sedekah which is stipulated for institutions that manage zakat, infaq and alms funds as their main activities. The purpose of this study was to determine whether BAZNAS Pematang Siantar had complied with PSAK 109 concerning zakat and infaq/alms accounting or not in preparing financial statements. This study uses a qualitative descriptive type of research, this research was conducted at BAZNAS Pematang Siantar City, the technique used in this study was a literature study and documentation technique. The results and conclusions of this study are that BAZNAS Pematang Siantar City has not used PSAK 109 in the preparation of its financial statements. The form of financial reports used by the Pematang Siantar City BAZNAS office is a report on receipts and distribution of funds and administrative expenses.